👤

0. The 7th, 8th and 94 terms of a sequence are 61, 69 and 77 respectively. Find the formula that describe the sequence.​

Sagot :

Answer:

Correct answer:

Correct answer:31

Correct answer:31Explanation:

Correct answer:31Explanation:Let d be the common difference, and let x be the second term. The first three terms are, in order, x−d,x,x+d.

Correct answer:31Explanation:Let d be the common difference, and let x be the second term. The first three terms are, in order, x−d,x,x+d.The sum of the first three terms is (x−d)+x+(x+d)=111.

Correct answer:31Explanation:Let d be the common difference, and let x be the second term. The first three terms are, in order, x−d,x,x+d.The sum of the first three terms is (x−d)+x+(x+d)=111.x+x+x+d−d=3x=111

Correct answer:31Explanation:Let d be the common difference, and let x be the second term. The first three terms are, in order, x−d,x,x+d.The sum of the first three terms is (x−d)+x+(x+d)=111.x+x+x+d−d=3x=111x=1113=37

Correct answer:31Explanation:Let d be the common difference, and let x be the second term. The first three terms are, in order, x−d,x,x+d.The sum of the first three terms is (x−d)+x+(x+d)=111.x+x+x+d−d=3x=111x=1113=37Now we know that the second term is 37. The fourth term is the second term plus twice the common difference: x+2d. Since the second and fourth terms are 37 and 49, respectively, we can solve for the common difference.

Correct answer:31Explanation:Let d be the common difference, and let x be the second term. The first three terms are, in order, x−d,x,x+d.The sum of the first three terms is (x−d)+x+(x+d)=111.x+x+x+d−d=3x=111x=1113=37Now we know that the second term is 37. The fourth term is the second term plus twice the common difference: x+2d. Since the second and fourth terms are 37 and 49, respectively, we can solve for the common difference.x+2d=37+2d=49

Correct answer:31Explanation:Let d be the common difference, and let x be the second term. The first three terms are, in order, x−d,x,x+d.The sum of the first three terms is (x−d)+x+(x+d)=111.x+x+x+d−d=3x=111x=1113=37Now we know that the second term is 37. The fourth term is the second term plus twice the common difference: x+2d. Since the second and fourth terms are 37 and 49, respectively, we can solve for the common difference.x+2d=37+2d=492d=12

Correct answer:31Explanation:Let d be the common difference, and let x be the second term. The first three terms are, in order, x−d,x,x+d.The sum of the first three terms is (x−d)+x+(x+d)=111.x+x+x+d−d=3x=111x=1113=37Now we know that the second term is 37. The fourth term is the second term plus twice the common difference: x+2d. Since the second and fourth terms are 37 and 49, respectively, we can solve for the common difference.x+2d=37+2d=492d=12d=6

Correct answer:31Explanation:Let d be the common difference, and let x be the second term. The first three terms are, in order, x−d,x,x+d.The sum of the first three terms is (x−d)+x+(x+d)=111.x+x+x+d−d=3x=111x=1113=37Now we know that the second term is 37. The fourth term is the second term plus twice the common difference: x+2d. Since the second and fourth terms are 37 and 49, respectively, we can solve for the common difference.x+2d=37+2d=492d=12d=6The common difference is 6. The first term is x−d=37−6=31.

Step-by-step explanation:

make me brainlest pls